Penyuluhan Hukum Pencegahan Pernikahan Dini di Desa Ngujung Kecamatan Maospati, Kabupaten Magetan - Purnama, Taufiq Yuli; Nugroho, Sigit Sapto; Haryani, Anik Tri (Fakultas Hukum Universitas Semarang, 2024)
The aim of this service is to provide understanding to the public about the factors that cause early marriage and efforts to prevent it. The method used is counseling and outreach regarding legal regulations regarding marriage and efforts to prevent early marriage. The causes of early marriage include economic factors, family, promiscuity and low levels of education, which have an impact on the increasing number of children dropping out of school, especially girls, violence against women, maternal and infant deaths, the community responds positively to the prevention efforts made by young women's leadership organizations. To anticipate the occurrence of underage marriages, the government together with religious leaders and community organizations need to socialize the Marriage Law to the community. Apart from that, there is also a need for the role of parents, the role of schools and teachers, the role of government and society in preventing early marriage in Ngujung Village, Maospati District, Magetan Regency. Efforts to prevent early marriage are carried out by holding outreach in the form of counseling regarding the impact of early marriage on the future of children. There are several factors for early marriage, including economic factors, economic factors, mass media factors, biological factors, out-of-wedlock pregnancy factors, traditional factors. Gather community and public support, and encourage the formation of regulations to prevent and eliminate child marriages under the age of 18.